2007
DOI: 10.1073/pnas.0701916104
|View full text |Cite
|
Sign up to set email alerts
|

PACT is a negative regulator of p53 and essential for cell growth and embryonic development

Abstract: The tumor suppressor p53 regulates cell cycle progression and apoptosis in response to various types of stress, whereas excess p53 activity creates unwanted effects. Tight regulation of p53 is essential for maintaining normal cell growth. p53-associated cellular protein-testes derived (PACT, also known as P2P-R, RBBP6) is a 250-kDa Ring finger-containing protein that can directly bind to p53. PACT is highly up-regulated in esophageal cancer and may be a promising target for immunotherapy. However, the physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 29 publications
2
86
0
2
Order By: Relevance
“…Transcriptional activation of p53 is also repressed by p202 via binding to the PXXP motifs of p53 (39) and by LSD1 through demethylated p53 protein (31). Notably, HSP27 and PFTm function as small-sized protein inhibitors of p53 by promoting the assembly of p53 into complexes (6,15,40). Here, we describe the novel functioning of BCAS2 as a smallsized p53 binding protein, not previously known to be a p53 inhibitor.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Transcriptional activation of p53 is also repressed by p202 via binding to the PXXP motifs of p53 (39) and by LSD1 through demethylated p53 protein (31). Notably, HSP27 and PFTm function as small-sized protein inhibitors of p53 by promoting the assembly of p53 into complexes (6,15,40). Here, we describe the novel functioning of BCAS2 as a smallsized p53 binding protein, not previously known to be a p53 inhibitor.…”
Section: Discussionmentioning
confidence: 85%
“…It is interesting to examine whether BCAS2 plays as a scaffold or adaptor molecule to mediate MDM2 or other E3 ligase-related proteins for p53 protein degradation. Various negative apoptotic regulators of p53 were recently identified that reduce p53 protein activity through different mechanisms (6,8,14,15,21,(36)(37)(38)(39)(40)(41)(42). For example, MDM2, PACT, aurora kinase A, and E6 function by causing p53 protein ubiquitination and degradation (6,13,33,43).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mpe1 has been implicated in regulating ubiquitination of PAP and potentially other factors (Lee and Moore 2014). Rbbp6 has also been shown to possess E3 ligase activity and function as an activator of Mdm2-mediated ubiquitination of p53 (Li et al 2007;Miotto et al 2014). Finally, a splice isoform of Rbbp6, called iso3 and consisting solely of the DWNN, competes with the full-length protein to modulate cleavage efficiency (Di Giammartino et al 2014).…”
Section: Rbbp6 and Pas Recognitionmentioning
confidence: 99%
“…RBBP6 interferes with binding of p53 to DNA and also facilitates interaction between p53 and its negative regulator, Mdm2, leading to enhanced p53 ubiquitination and degradation. Moreover, disruption of RBBP6 in mice leads to early embryonic lethality, but a p53-null mutation partially rescues viability (Li et al 2007). The RBBP6 C-terminal region contains domains responsible for interaction with both tumor suppressors.…”
mentioning
confidence: 99%